SiO2 etching in inductively coupled plasmas using heptafluoroisopropyl methyl ether and 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether - Kim, Jun Hyun; Park, Jin Su; Kim, Chang Koo (Applied Surface Science, 2020)
Heptafluoroisopropyl methyl ether (HFE-347mmy) and 1,1,2,2-tetrafluoroethyl 2,2,2-trifluoroethyl ether (HFE-347pcf2), whose global warming potentials are significantly lower than those of perfluorocompounds, are used for plasma etching of SiO2. The SiO2 etch rates are higher in the HFE-347mmy/Ar plasma than in the HFE-pcf2/Ar plasma owing to the larger production of CF2 radicals and corresponding formation of thicker fluorocarbon films on the substrate surface in the HFE-347pcf2/Ar plasma than in the HFE-347mmy/Ar plasma. The angular dependences of the etch rates at various bias voltages (−400 to −1200 V) are measured using a Faraday cage. The normalized etch yields (NEYs) have the maxima at ion incidence angles between 50° and 60° in both plasmas at all bias voltages. The NEYs increase with the bias voltage up to −800 V, and then virtually follow a single curve for bias voltages higher than −800 V in HFE-347mmy/Ar, while they continuously increase with the bias voltage in the range of −400 to −1200 V in HFE-347pcf2/Ar. The dependences of the NEYs of SiO2 on the ion incidence angle and bias voltage in both plasmas are explained by analyzing the thicknesses and fluorine-to-carbon ratios of the steady-state fluorocarbon films formed on the substrate surfaces.
Keywords: Angular dependence; Etch yield; Faraday cage; Fluorocarbon films; Global warming potential; Ion incidence angle; Perfluorocompounds; Substrate surface; Angular dependence; Etch yield; Faraday cage; SiO2 etching; Steady-state fluorocarbon film